Frailty and chronic respiratory disease: the need for a multidisciplinary care model - Symvoulakis, Emmanouil; Kamekis , Apostolos; Drakonaki, Elena Drakonaki; Mastrodemou, Semeli; Ryerson, Christopher J. Ryerson5; Antoniou, Katerina (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2021)
Background. Frailty is a state of increased vulnerability to various health stressors but little information is summarized about frailty in people with specific chronic respiratory diseases such as chronic obstructive pulmonary disease (COPD), idiopathic pulmonary fibrosis (IPF), and asthma. Methods. PubMed and Cochrane Central databases were systematically reviewed for studies reporting outcomes associated with frailty in COPD, IPF, and asthma. Electronic databases were searched for relevant articles published in English from 2010 up to July 2020. Appraisal was carried out based on the Hierarchy of Evidence Rating System and the GRADE guidelines. Results. A total of 31 articles met all inclusion criteria with 25 of them at level IV, 1 at level V, and 5 at level VI. Frailty is likely to negatively affect quality of life and to increase the risk of mortality, especially in elderly with COPD, IPF and asthma. Each disease has a particular effect on the balance between health status, respiratory impairment and frailty. A greater understanding of frailty phenotype across different ages, as well as in a range of long-term conditions, is of great necessity in both clinical and research settings. Limited conformity was observed between different methodologies and nature of chronic diseases studied, leading to a further difficulty to extract homogeneous information. Conclusion. Literature shows that frailty is prevalent in COPD, IPF, and asthma, after adjusting for shared risk factors. Our findings suggest that frailty should be approached as an entity per se’, in order to assess real mortality risk, alongside respiratory disease severity and the presence of comorbidities. Health care professionals need knowledge, skills and multidisciplinary collaboration to buffer the impact of frailty on everyday practice.